Reshaping the global economy - Jean Pisani-Ferry; Indhira Santos (Bruegel, 2009)
Jean Pisani-Ferry and Indhira Santos observe that the crisis and the national responses to it have started to reshape the global economy. But beyond the specifics of shock transmission, the crisis has also exposed that, in spite of regional integration and the emergence of new economic powers, the global economy lacks resilience. The authors explain how they believe the international community could build a stronger and more legitimate globalised governance out of the crisis.
Keywords: 330; Finanzmarktkrise; Wirtschaftskrise; Weltwirtschaftspolitik; Internationale wirtschaftspolitische Koordination; Globalisierung; G-20-Staaten